MEKANISME DAN HAMBATAN PENYELESAIAN PERKARA PIDANA MELALUI KEADILAN RESTORATIF - Pranowo, Johannes Bagus; Markoni, Markoni; Helvis, Helvis; Kantikha, I Made; Elawati, Tuti (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The renewal of the Indonesian Criminal Procedure Code (New KUHAP) marks a paradigm shift in criminal law enforcement by integrating restorative justice as an integral part of the criminal procedure system. This approach is explicitly regulated in Articles 83 to 87 of the New KUHAP, which provide opportunities for resolving criminal cases through agreements between victims and offenders at the stages of inquiry, investigation, prosecution, and court examination. This study applies the criminal justice system theory to analyze the integration of authority among law enforcement institutions, as well as restorative justice theories proposed by Howard Zehr, Tony F. Marshall, Muladi, and Barda Nawawi Arief to assess the orientation toward victim and offender restoration in criminal case resolution. The research employs a normative legal method using statutory and conceptual approaches, examining the New KUHAP along with relevant regulations issued by the Indonesian National Police, the Attorney General’s Office, and the Supreme Court. The findings indicate that the New KUHAP establishes a more systematic, structured, and binding restorative justice framework, including mechanisms for terminating inquiry, investigation, and prosecution under the supervision of prosecutors and courts. The study concludes that the effective implementation of restorative justice depends not only on legal norms but also on institutional harmonization, the readiness of law enforcement officials, and the active participation of both victims and offenders. Keywords: Criminal Justice System, Restorative Justice. Abstrak: Pembaruan Kitab Undang-Undang Hukum Acara Pidana (KUHAP Baru) menandai perubahan paradigma penegakan hukum pidana di Indonesia dengan mengintegrasikan keadilan restoratif sebagai bagian dari mekanisme hukum acara pidana. Hal ini tercermin dalam Pasal 83 sampai Pasal 87 KUHAP Baru yang membuka ruang penyelesaian perkara pidana melalui kesepakatan antara korban dan pelaku pada tahap penyelidikan, penyidikan, penuntutan, hingga persidangan. Penelitian ini menggunakan teori sistem peradilan pidana untuk menganalisis keterpaduan kewenangan antar lembaga penegak hukum serta teori keadilan restoratif dari Howard Zehr, Tony F. Marshall, Muladi, dan Barda Nawawi Arief untuk menilai orientasi pemulihan dalam penyelesaian perkara pidana. Metode penelitian yang digunakan adalah penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual melalui kajian terhadap KUHAP Baru serta peraturan Kepolisian, Kejaksaan, dan Mahkamah Agung. Hasil penelitian menunjukkan bahwa KUHAP Baru membentuk kerangka keadilan restoratif yang lebih sistematis, terstruktur, dan mengikat dengan mekanisme penghentian perkara di bawah pengawasan penuntut umum dan pengadilan. Kesimpulan penelitian menegaskan bahwa keberhasilan keadilan restoratif bergantung pada harmonisasi antar lembaga, kesiapan aparat, dan partisipasi aktif korban serta pelaku. Kata kunci: Keadilan restoratif, Sistem Peradilan Pidana